Program Optimalisasi Peran Laboratorium Fisika SMA di Kota Metro, Lampung - Nyoto Suseno; Riswanto Riswanto (Jurnal Pengabdian Pada Masyarakat, 2017)
THE ROLE OPTIMIZATION PROGRAM OF PHYSICAL LABORATORY OF SENIOR HIGH SCHOOL IN METRO CITY, LAMPUNG. The Government Regulation (PP) of the Republic of Indonesia no. 19 of 2005 sets eight educational standards. The results survey found every high school in Metro City has been equipped with physics laboratory and has formed an organizational structure. But the physics laboratory to support the learning process, has not been done well. The purpose of this IbM (Ipteks bagi Masyarakat) Program is to apply theory and concept of Laboratory management in order to optimize the role of Physics Laboratory to supporting the learning process. The methods used are: Making of laboratory inventory website, workshop of the standard making of laboratory management, facilitation of website and arrangement of laboratory apparatus, workshop of making work program, workshop of making service, and doing simulation result of the workshop. The results obtained are: 1) Generally the condition of high school physics laboratory in Metro City has exceeded the standard up to 71,9%; 2) Aspects that do not meet government standards are no technicians and less on electric and sink socket facilities of 5,7%; 3) Utilization of high school laboratory inventory website gives a quite effective and significant impact in assisting the administration of laboratory equipment and facilitate access in tracking the existence of physics laboratory equipment and materials.